Smart precision agriculture but resource constrained farmers: Is service provision a potential solution? Farmer's willingness to pay for laser-land leveling services in Nepal - Paudel, Gokul Prasad; Khanal, Aditya Raj; Rahut, Dil Bahadur; Krupnik, Timothy J.; McDonald, Andrew J. (Elsevier, 2023)
Farmers commonly split large, undulating crop fields, even those at similar elevation range or contour, into a patchwork of small sub-plots in plane areas of Nepal. Specifically, to ensure irrigation or rainwater throughout their cultivated rice or wheat growing areas, structures like bunds, dikes, and ditches are commonly built. These structures not only require significant labor hours to build but also incur loss of some portion of productive crop areas. Laser-land leveling (LLL) is one of the precision technologies that can prevent these area losses, save labor costs, and enhance water utilization. However, purchase of LLL system requires significant capital which could be beyond the access of low resource farmers. In this study, we examined the potential of LLL adoption in a form of service provision or fee-for-service basis among farmers in Nepal. Using an appropriate contingent valuation that maintains efficient estimation and consistent response, we found that Nepali farmers’ willingness to pay (WTP) for LLL services averages 1,550 Nepalese Rupees per hour. However, WTP is heterogeneous across farm size—top quantile farmers with relatively higher land acreages have 47% higher WTP for LLL than bottom quantile farmers. Additionally, our interval regression results show positive association of WTP with low irrigation access and with the opportunity cost of land area occupied by bunds and dikes. The results suggest for service provision support programs in LLL adoption to enhance market development of this precision technology in Nepal, specifically focusing land holders with low irrigation access in plane areas.